2014
DOI: 10.1242/jcs.139337
|View full text |Cite
|
Sign up to set email alerts
|

Immune synapse targeting of specific recycling receptors by the intraflagellar transport system

Abstract: T cell activation requires sustained signaling at the immune synapse, a specialized interface with the antigen-presenting cell (APC) that assembles following T cell antigen receptor (TCR) engagement by major histocompatibility complex (MHC)-bound peptide. Central to sustained signaling is the continuous recruitment of TCRs to the immune synapse. These TCRs are partly mobilized from an endosomal pool by polarized recycling. We have identified IFT20, a component of the intraflagellar transport (IFT) system that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(144 citation statements)
references
References 57 publications
8
133
0
2
Order By: Relevance
“…S8). The KPL-IFF model may implicitly be capturing TCR surface dynamics because directed movement (47) combined with polarized recycling (48,49) of TCR into the immune synapse may balance with TCR internalization (46) to maintain the relatively constant TCR concentration at the immune synapse assumed by the KPL-IFF model, which is consistent with previous calculations (50). A recent study has shown that changing the pMHC affinity can induce a program that over a timescale of several days changes TCR levels (51).…”
Section: Fig 4 Systematic Analyses Of Signaling Models Reveals Thatmentioning
confidence: 99%
“…S8). The KPL-IFF model may implicitly be capturing TCR surface dynamics because directed movement (47) combined with polarized recycling (48,49) of TCR into the immune synapse may balance with TCR internalization (46) to maintain the relatively constant TCR concentration at the immune synapse assumed by the KPL-IFF model, which is consistent with previous calculations (50). A recent study has shown that changing the pMHC affinity can induce a program that over a timescale of several days changes TCR levels (51).…”
Section: Fig 4 Systematic Analyses Of Signaling Models Reveals Thatmentioning
confidence: 99%
“…This finding raises the possibility that IFT20 might participate in intracellular membrane trafficking, in addition to its role in ciliary assembly. Supporting this hypothesis, recent studies have demonstrated that IFT20 is associated with the trafficking of ciliary membrane proteins from the Golgi to the cilium, opsin trafficking, and membrane trafficking in lymphoid and myeloid cells (18,19,33,48); however, it remains unclear whether IFT20 functions as a noncanonical IFT system during craniofacial skeletal development. Ift20:Wnt1-Cre embryos showed immature bone mineralization (Fig.…”
Section: Ift20 Is Critical For Regulating the Trafficking Of Procollamentioning
confidence: 99%
“…Supporting this idea, the deletion of Ift20 in mouse kidney causes a lack of primary cilia and leads to polycystic kidney disease (17). In addition to the traditional role of IFT in cilium assembly, recent studies have found that an IFT-like particle organized by IFT20 is recruited to the immune synapse for T-cell receptor recycling (18,19). These studies suggest that IFT proteins participate in intracellular membrane trafficking in immune cells; however, it remains unclear how IFT20 governs developmental processes, including skeletal formation, and how it functions in other cell types, such as multipotent stem cells.…”
mentioning
confidence: 98%
“…We have recently shown that IFT20 colocalizes in part with Rab11 in T-cells (Finetti et al, 2014), raising the possibility that IFT20 and Rab8 might associate at Rab11 + endosomes. Immunofluorescence analysis showed indeed a significant colocalization of IFT20 with Rab8 (Fig.…”
Section: Rab8 Colocalizes With Rab11 and Ift20 At A Pericentrosomal Cmentioning
confidence: 99%
“…Moreover the TCR can be found in endosomes marked by Rab35 and its GAP EPI64C (Patino-Lopez et al, 2008). We have recently demonstrated that IFT20, a component of the intraflagellar transport (IFT) system that is responsible for the assembly and maintenance of cilia and flagella (Pazour and Bloodgood, 2008;Pedersen and Rosenbaum, 2008), is a central regulator of the pathway that regulates TCR recycling (Finetti et al, 2009), interacting with Rab5 to promote TCR trafficking from early endosomes (Finetti et al, 2014).…”
Section: Introductionmentioning
confidence: 99%